O’ZBEKISTONDA QON SO’RUVCHI-TASHUVCHI HYALOMMA (IXODIDAE) AVLODI KANALARINI O’RGANILISHI - Sobirova H.S., Sobirova H.S. (Actual problems and prospects of the study of the fauna, 2024)
This article provides information on the study of ants of the sucker-carrier Hyalomma (Hyalomma) generation in Uzbekistan, as well as information on their quality, biology and ecological characteristics